2023
DOI: 10.1177/09603271231180849
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera Alter BCL2/Bax signaling and trigger apoptosis of MCF-7 and MDA-MB231 breast cancer cells exposed to γ-radiation

Abstract: Treatment strategies encompass synchronization of more than one therapy with specific dependence on zeroing side effects of natural products that might represent a niche in the continuous struggle against cancer. Thus, this study aimed at assessing the role of Withania somnifera; WS (Ashwagandha) in forcing MCF7 or MDA-MB 231 irradiated breast cancer cells to outweigh the route of programmed cell death. We check to what extent SIRT1-BCL2/Bax signaling pathway was interrelated to form apoptotic cancer cells. MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…9 , in MCF-7 both compounds showed a better performance, measured as a decrease in the percentage of cell viability, than Gossypol, in a concentration-dependent manner without involving the cell number seeded; this finding is an outstanding insight into the probable mechanism of action conducted by 6 and 37 which points mainly to a probable Bcl-2 inhibition, reinforced for a GPER modulation, since, from the energetical analyzes yielded by in silico simulations over the two pharmacological targets, the affinity of both compounds is slightly more representative for GPER in comparison with Bcl-2 (< onefold), however, from the individual results analysis, 37 decreased cell proliferation in a better way than 6 probably due to the slightly finer binding energy of this ligand towards Bcl-2 as is possible to contrast it both docking calculations and molecular dynamics simulations. Astoundingly, MDA-MB-231 cancer cell were more sensitive to the assayed compounds than MCF-7 cells, owing largely to a over expression of Bcl-2 protein on MDA-MB-231 cell line 64 , 65 , added to a slight GPER expression that in a basal state, triggers proliferation and cancer cell survival 66 , 67 , although, from the individual results obtained for MCF-7 cancer cells, 37 depicted an IC 50 value significantly lower than Gossypol (18.66 vs. 65.67 μM, respectively), probably due to multiple effects of this ligand at inhibit both estrogen receptors (ERs α > β and GPER) and the anti-apoptotic protein Bcl-2, triggering a synergistic effect which leads to a best antiproliferative performance than showed by Gossypol, besides, we were unable to determine the IC 50 value for G-15, due to solubilization problems starting at a 20 μM concentration (Data not showed). The highlighted above place both compounds as potential therapeutic options against most aggressive cancer type TNCB (Triple-Negative Breast Cancer) represented by the two cancer cell lines assayed.…”
Section: Resultsmentioning
confidence: 99%
“…9 , in MCF-7 both compounds showed a better performance, measured as a decrease in the percentage of cell viability, than Gossypol, in a concentration-dependent manner without involving the cell number seeded; this finding is an outstanding insight into the probable mechanism of action conducted by 6 and 37 which points mainly to a probable Bcl-2 inhibition, reinforced for a GPER modulation, since, from the energetical analyzes yielded by in silico simulations over the two pharmacological targets, the affinity of both compounds is slightly more representative for GPER in comparison with Bcl-2 (< onefold), however, from the individual results analysis, 37 decreased cell proliferation in a better way than 6 probably due to the slightly finer binding energy of this ligand towards Bcl-2 as is possible to contrast it both docking calculations and molecular dynamics simulations. Astoundingly, MDA-MB-231 cancer cell were more sensitive to the assayed compounds than MCF-7 cells, owing largely to a over expression of Bcl-2 protein on MDA-MB-231 cell line 64 , 65 , added to a slight GPER expression that in a basal state, triggers proliferation and cancer cell survival 66 , 67 , although, from the individual results obtained for MCF-7 cancer cells, 37 depicted an IC 50 value significantly lower than Gossypol (18.66 vs. 65.67 μM, respectively), probably due to multiple effects of this ligand at inhibit both estrogen receptors (ERs α > β and GPER) and the anti-apoptotic protein Bcl-2, triggering a synergistic effect which leads to a best antiproliferative performance than showed by Gossypol, besides, we were unable to determine the IC 50 value for G-15, due to solubilization problems starting at a 20 μM concentration (Data not showed). The highlighted above place both compounds as potential therapeutic options against most aggressive cancer type TNCB (Triple-Negative Breast Cancer) represented by the two cancer cell lines assayed.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry analysis revealed that in the experimental group, consisting of MDA-MB-231 and MCF7 breast cancer cell lines treated with Withania prior to irradiation, there was an increased percentage of apoptotic cells (including early, late, and necrotic cells) compared to the control group, which only received irradiation. Additionally, it altered BCL2/Bax signal transduction and triggered apoptosis in breast cancer cells exposed to γ radiation ( 147 ).…”
Section: Traditional Chinese Medicine and Radiotherapy Resistancementioning
confidence: 99%